Serum Soluble Endoglin in Asymptomatic Primary Hyperparathyroidism: A Case-Control Study: sENG in Asymptomatic PHPT - ÇORDAN, ilker; Deniz, Çiğdem Damla (Journal of Medical Biochemistry, 2026)
Background: Primary hyperparathyroidism (PHPT) is associated with metabolic disorders, endothelial dysfunction, and increased cardiovascular risk. Soluble endoglin (sENG), an endothelium-derived biomarker, is a potential indicator of TGF-β-related vascular stress. This study aimed to compare serum sENG levels between patients with asymptomatic PHPT and healthy controls and to evaluate the association between sENG and metabolic parameters. Methods: This cross-sectional study included 42 patients with biochemically confirmed asymptomatic PHPT and 39 age- and sex-matched healthy controls.  Serum sENG levels and metabolic parameters were compared between groups. Welch t-test, chi-square test, correlation, and regression analyses were used to evaluate potential associations.Results: Serum sENG levels were similar in the PHPT and control groups (1.40±1.13 vs. 1.46±1.31 ng/mL, p=0.83). In the PHPT group, weak-to-moderate positive trends were observed between sENG and body mass index, fasting glucose, insulin, and HOMA-IR, whereas these trends were less pronounced in controls. In linear regression analysis, body weight was identified as an independent determinant of sENG in the PHPT group (p=0.047). In two-way ANOVA, no significant main or interaction effects were detected; however, borderline interaction trends were observed for glucose and body mass index.Conclusion: Serum sENG levels did not differ significantly between asymptomatic PHPT and control groups. However, the observed trends between sENG and metabolic parameters in patients with PHPT suggest that sENG may reflect early interactions between metabolic burden and endothelial response even in the absence of a marked biochemical increase. Larger prospective studies may clarify the clinical and pathophysiological significance of sENG in PHPT.